Wettability effect of PECVD-SiOxfilms on poly(lactic acid) induced by oxygen plasma on protein adsorption and cell attachment - S. Sarapirom (2018)
Surface wettability is an important property of biomaterials. Silicon oxide films have a wide range of applications due to a range of the properties such as the mechanical strength and surface wettability. This paper reports effect of the surface wettability of silicon oxide (SiO x ) films on protein adsorption and cell attachment and proliferation. SiO x films were deposited onto poly(lactic acid) (PLA) substrate using plasma enhanced chemical vapor deposition (PECVD). Octamethylcyclotetrasiloxane (OMCTS:Si 4 O 4 C 8 H 24 ) was used as a precursor with O 2 as a carrier gas. After deposition, the films were treated with O 2 -plasma to adapt wettability. It was found that O 2 -plasma enhanced the wettability of the films without changing the film thickness, while made the surface morphology slightly smoother. The polar component increased after O 2 -plasma treatment as observed in the contact angle measurements. The surface energy of the films was calculated by means of the Owens-Wendt method to resolve the contributions of polar and dispersive components. The chemical structure was characterized using attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy. The films were dense with a high Si-network structure. The reduced carbon content (-CH n , Si-CH 3 ) and increased hydrogen content (-OH) of the O 2 -plasma treated SiO x films led to the polar components enhancing the SiO x wettability. Adsorption of bovine serum albumin (BSA) on the films was investigated by using x-ray photoelectron spectroscopy (XPS). More BSA was adsorbed onto the O 2 -plasma treated SiO x films. Attachment and proliferation of MC3T3-E1 mouse pre-osteoblasts and L929 mouse fibroblasts cells on the SiO x films were evaluated via MTT assay. The cells were attached more to the untreated SiO x films but proliferated more on the surface of the O 2 -plasma treated SiO x films depending on the cell types. © IOP Publishing Ltd 2013.